Sustainable Halal Tourism in The Post Pandemic Era: Opportunity and Challenges - Cyntia Keliat; I Gede Eko Putra Sri Sentanu (Journal of Research on Business and Tourism, 2022)
The Halal Industry is the fastest growing industry in the global economy with a large annual growth rate. This segment of Halal Tourism is very promising before 2020 even predicted will be higher by the time. However, the sustainability of Halal Tourism has to be questioned since the pandemic hit the world which creates many conditions of uncertainty. This study aims to investigate sustainable halal tourism in the post pandemic era. The methodology that is using here is literature review technique. The results of this study are expected to be able to contribute some facts for the currently situation and the upcoming situation after pandemic.